Forming a peaceful mindset in the BANI era: A systematic literature review of Cognitive Behavioral Therapy interventions - Muh. Syawal Hikmah; Nur Hidayah; Fitri Wahyuni; Abi Fa’izzarahman Prabawa (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2025)
The phenomenon of the BANI era (Brittle, Anxiety-Inducing, Non-linear, and Incomprehensible), characterized by uncertainty, psychological pressure, and social disruption, demands therapeutic approaches that foster peaceful thinking and awareness, emotional regulation, and inner balance. This study aims to identify the developmental trends of Cognitive Behavioral Therapy (CBT) over the past 15 years in cultivating a peaceful mindset in individuals and to examine the techniques used within CBT interventions to achieve this goal. The research employs a Systematic Literature Review (SLR) method following the PRISMA stages, including identification, screening, eligibility, and inclusion processes. From 1,197 articles identified through the Scopus and Google Scholar databases, 11 final articles published between 2010 and 2025 met the inclusion criteria. The findings reveal that CBT has evolved from a conventional clinical approach into more diverse forms, encompassing trauma healing, empowerment-based CBT, social-humanistic, integrative (such as MBCT and ACT), community-based CBT, social-structural, existential, educational-curative, transcendental-spiritual, and AI-integrated digital approaches. Furthermore, the study identifies five main techniques that contribute most significantly to fostering a peaceful mindset: cognitive restructuring, cognitive reframing, mindfulness, relaxation training, and behavioral activation. These findings emphasize that CBT is not merely a clinical therapy but a transformative psychological strategy that cultivates both intrapersonal and interpersonal peace. Therefore, CBT holds strong potential to be developed as an integrative peace-based therapy relevant for enhancing mental well-being and individual resilience amid the complexities of the BANI era.